Socio-cultural and governance foundations of successful income-generating groups in pastoral societies: Evidence from northern Kenya. Issue 4 (7th August 2020) - Arasio, Raphael Lotira; Kaufmann, Brigitte; Wasonga, Oliver Vivian; Otieno, David Jakinda
ABSTRACT: Many community groups in rural Africa malfunction or collapse after external support has ended. The use of non-consultative and non-contextual approaches in the establishment and evaluation of community groups has been associated with limited understanding of group functionality. This paper uses the perspectives of group members to identify social and governance factors contributing to the performance of pastoral income-generating groups. Self-assessment of performance was done with 153 groups followed by 18 semi-structured and 10 to 18 in-depth interviews with well-functioning groups. The results explain and contextualize the importance of specific member characteristics with regard to combining capabilities and resources to increase collective action options of the groups. Group members modified externally provided guidelines on group governance to conform them to traditional governance practices. These insights emphasize the importance of knowledge on socio-cultural norms and practices, and the consideration of experiences and perceptions of community members when establishing community groups.